ANALISA PENERIMAAN PENGGUNA SISTEM INFORMASI KOPERASI PADA KOPERASI KARYAWAN BUDI SETIA JAKARTA DENGAN TECHNOLOGY ACCEPTANCE MODEL - Mahendra, Irfan (LPPM Universitas Nusa Mandiri, 2015)
This research aims was to measure and analyze user acceptance of Sistem Informasi Koperasi (Siskop) in Koperasi Karyawan Budi Setia Jakarta, using Technology Acceptance Model (TAM). This research is quantitative research. Meanwhile, according to the the characteristics of the problem, this research included in exploratory research, descriptive research, and explanatory research. The data used in this research are primary data and secondary data, collected using several data collection techniques, such as observation, questionnaires, document review, and literature review. The variables in this research are independent variables; perceived ease of use - PEOU, intervening variables; perceived of usefullness - PU, attitude toward using - ATU, and behavioral intention to use - BIU, and the dependent variable; actual use - AU. Processing and analysis of data in this research was using descriptive statistics analysis and simple linear regression analysis, which done by the support of the Application SPSS version 21 for Windows. The results of this research are as follows 1) perceived ease of use have given positive and significant influence to perceived usefulness and attitude toward using Siskop; 2) perceived usefulness Siskop given positive and significant influence to attitude toward using Siskop, behavioral intention to use, and actual Siskop use; 3) attitude towards using Siskop positive and significant influence to behavioral intention to use Siskop. However 4) behavioral intention to use Siskop did not has a signicant influences to actual Siskop use.